Institutional Approach: Legal Protection Efforts against Sexual Violence in Islamic Boarding School Educational Institutions - Ahmad Jamaludin (UIN Sunan Gunung Djati, 2025)
The increasing number of pesantren and students reflects the rapid growth of these institutions over recent decades. The high number of students in religious-based educational institutions, such as pesantren, with their complex interactions involving children and the need for controlled environments, has been shown to increase vulnerability to sexual violence. This is evidenced by the occurrence of 12 cases of child sexual abuse between January and July 2022, with pesantren being the most frequent location, accounting for 5 cases (41.67%). Using an institutional approach, this paper aims to provide an alternative perspective on improving policies and procedures to enhance the effectiveness of preventing and addressing sexual violence in pesantren. Previous research by Pebriaisyah et al. focused on the power dynamics between kyai and female students in pesantren, highlighting patterns of abuse and proposing sexual education as a preventive measure. In contrast, this study emphasizes policy reform through institutional guidelines to prevent sexual violence. The key difference is that this study addresses broader policy aspects, while Pebriaisyah’s work is more specific to individual dynamics. The research employs a mixed-methods approach, combining quantitative and qualitative data, with primary data collected through online questionnaires from adolescents aged 14-17 during March 2023, and a normative juridical analysis using primary and secondary legal materials to analyze the prevention and handling of sexual violence in pesantren according to relevant laws and regulations. The findings conclude that, first, the authoritative nature of educational institutions in preventing and addressing sexual violence increases the likelihood of institutional leaders acting arbitrarily, often protecting perpetrators and neglecting victims. Second, the institutional approach can be implemented gradually, from preventive to responsive measures, through the development of multidisciplinary protocols and strategies specific to preventing and addressing sexual violence. Ultimately, a comprehensive legal framework will provide a foundation for task forces to act as the primary implementers of policies in preventing and handling sexual violence in pesantren.